Posterior Lumbar Interbody Fusion with Spinal Decompression using Minimally Invasive Spine Surgery in the Treatment of Symptomatic Degenerative Spinal Stenosis - Silaban, Michael Rothmans; Kadar, Pranajaya Dharma (Open Access Macedonian Journal of Medical Sciences, 2021)
Introduction Lumbar spinal stenosis is often the result of advanced degeneration of motion segments of the lumbar spine. The incidence of this case is 3.57% (3570 per 100,000) population in Southeast Asia. The main symptoms are low back pain, numbness, and weakness in the lower extremity that occur and intensify on walking caused by the load of the body weight on the spine. Loss of disc height, facet displacement and hypertrophy, spondylosis, and spondylolisthesis , all contribute to impact the spinal canal and intervertebral foramen in lumbar stenosis . There is a subgroup of patients with spinal stenosis in whom the spine is unstable preoperatively or become destabilized following decompression who would benefit from fusion procedure. Objective Surgical treatment of lumbar spinal stenosis by posterior lumbar interbody fusion is indicated for patients with symptoms of low back pain and lower limb radicular pain, that are unsuccessful treated with medicines and /or patients with persisting or worsening neurological deficit.However, this procedure may lead to possible complications. This case report study was conducted to show how our hospital handling spinal stenosis case. Case A 67-year-old woman presented with low back pain that has occured for two years, and had been worsening for the past 3 months. She described the pain as an intermitten ache down on her leg, the pain was severe and worsened when the patient is standing, sitting, or walking for a long time , The pain severity was measured by visual analog score (vas), graded between 7/10 to 9/10. She also complained numbness from the bilateral gluteal region to the lateral side of lower extremities, when she feel too tired. On the physical examination, She was found to have limited range of motion for flexion and extension, on the lumbar spine, due to pain. The motoric strength of both lower limbs were decreased, so did the sensory function. The Radiological examination showed a severe stenosis at lumbar spinal bone region on L4-L5 area. After the examination, the patient agreed to undergo the suggested operative procedure and gare the consent at the hospital.